U6,6 I svyerkhskhodyashchiyesya pravila summ dlya myezon-barionnogo rassyeyaniya - Jones,HF; Scadron,MD (Il Nuovo Cimento A, 1967)
Superconvergent sum rules are derived for πN→πN, two of which agree with U6,6 when saturated by N and N poles in the equal-mass limit. Saturation for physical masses gives GcyrillicN=84 MeV. It is pointed out that those sum rules which agree with U6,6 for πN→πN and πN→πN do so also for all analogous strange-particle reactions. The special status of these sum rules is discussed. © 1967 Società Italiana di Fisica.